Micro-systems mechanics VOLUME II - Lin, Rongming (2008)
Including: 3 parts. TiNi thin films have attracted much attention in recent years as intelligent and functional materials because of their unique properties. TiNi thin film based micro-actuators will become the actuator of choice in many aspects in the rapidly growing field of micro-electro-mechanical systems. In this report, TiNi and TiNiCu films were successfully prepared by co-sputtering of a TiNi target and a separate Ti or Cu targets. Some critical issues and problems in the successfully development of TiNi thin films were discussed, including preparation and characterization considerations, residual stress and adhesion, frequency improvement, fatigue and stability, patterning and modeling of behavior as well as functionally graded or composite thin films. Comparison was made of TiNi SMA microactuation with other microactuation methods. Different types of MEMS applications we have done so far (such as microgrippers, micropumps, micromirror, etc.) were reported and the prospects for future advances in fabrication process and device development were discussed.